Editor's Choice – Fenestrated or Branched Endovascular versus Open Repair for Complex Aortic Aneurysms: Meta-Analysis of Time to Event Propensity Score Matched Data. (February 2021) - Antoniou, George A.; Juszczak, Maciej T.; Antoniou, Stavros A.; Katsargyris, Athanasios; Haulon, Stephan
Abstract : Objective: The aim of this review was to investigate comparative outcomes of fenestrated or branched endovascular aneurysm repair (F/BEVAR) with open repair for juxta/para/suprarenal or thoraco-abdominal aortic aneurysms. Methods: Electronic bibliographic sources (MEDLINE and Embase) were interrogated using the Healthcare Databases Advanced Search interface. Eligible studies compared F/BEVAR with open repair for complex aortic aneurysms using propensity score or Cox regression modelling/multivariable logistic regression analysis. Pooled estimates of peri-operative outcomes were calculated using the odds ratio (OR) and 95% confidence interval (CI). The result of time to event analysis was reported as summary hazard ratio (HR) and 95% CI. Random effects models and the inverse variance method were applied. The quality of evidence was graded using the system developed by the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) working group. Results: Eleven studies published between 2014 and 2019 were selected for inclusion in qualitative and quantitative synthesis reporting a total of at least 7 061 patients. The odds of peri-operative mortality after F/BEVAR were lower, although not significantly, than after open repair (OR 0.56, 95% CI 0.28–1.12), whereas the hazard of overall mortality during follow up was higher following F/BEVAR, but, again, without reaching statistical significance (HR 1.25, 95% CI 0.93–1.67). The hazard of re-intervention was significantly higher after endovascular therapy (HR 2.11, 95% CI 1.39–3.18). The certainty for the body of evidence for peri-operative and overall mortality during follow up was judged to be very low and moderate, respectively, and for re-intervention it was judged to be high. Conclusion: The evidence is uncertain about the effect of F/BEVAR on peri-operative mortality when compared with open repair. There is probably no difference in overall survival, but F/BEVAR results in an increased re-intervention hazard. There is a need for high level evidence to inform decision making and vascular/aortic service provision.